2014
DOI: 10.1007/s10803-014-2178-7
|View full text |Cite
|
Sign up to set email alerts
|

Stress and Family Quality of Life in Parents of Children with Autism Spectrum Disorder: Parent Gender and the Double ABCX Model

Abstract: Past research has supported the utility of the Double ABCX model of family adaptation for parents raising a child with autism spectrum disorder (ASD). What remains unclear is the impact of family-related variables on outcomes in both mothers and fathers within the same family. We explored the potential predictors of maternal and paternal stress and family quality of life in an Australian sample of 196 parents of children with ASD aged 3-16 years. Using a cross-sectional design, parents completed questionnaires… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
166
1
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 232 publications
(187 citation statements)
references
References 52 publications
(135 reference statements)
13
166
1
7
Order By: Relevance
“…As primary caregivers, mothers are more likely to experience parenting related difficulties. One study that examined child related stressors, availability of resources, and coping strategies among parents of children with ASD found that mothers experienced higher levels of stress than fathers (McStay et al, 2014). Although parents of children with ASD use various coping styles, such as acceptance, humour, and gaining hope from child's improvement (Marshall & Long, 2010), some coping styles used may be counterproductive or maladaptive (Hall & Graff, 2011;Sivberg, 2002).…”
Section: Mothers' Experiences When There Is a Child With Asd In Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…As primary caregivers, mothers are more likely to experience parenting related difficulties. One study that examined child related stressors, availability of resources, and coping strategies among parents of children with ASD found that mothers experienced higher levels of stress than fathers (McStay et al, 2014). Although parents of children with ASD use various coping styles, such as acceptance, humour, and gaining hope from child's improvement (Marshall & Long, 2010), some coping styles used may be counterproductive or maladaptive (Hall & Graff, 2011;Sivberg, 2002).…”
Section: Mothers' Experiences When There Is a Child With Asd In Theirmentioning
confidence: 99%
“…These characteristics include age (Gray, 2006;Pruitt, Willis, Timmons, & Ekas, 2016), gender (Allik et al, 2006;Lee, 2009;McStay et al, 2014;Mugno et al, 2007), employment status (Dardas & Ahmad, 2014a), and household income (Dardas & Ahmad, 2014a). In fact, a recent review on coping styles among parents of children with ASD reported that age and gender of parents are the most commonly discussed factors (Lai & Oei, 2014).…”
mentioning
confidence: 99%
“…Researchers provided substantial evidence that the social impact of the child's disability [18] and challenging behaviours [19][20][21][22][23][24][25] in children with ASD or ID was associated with poorer care-giver mental health. At the same level of evidence, challenging child behaviours in children with ID were related to poorer care-giver physical health in subsequent years [26].…”
Section: Challenging Child Behaviormentioning
confidence: 99%
“…One research group administered the Parental-Developmental Disorders-Quality of Life Scale (Par-DD-QoL) to the parents of children with ASD and provided weak evidence that challenging child behaviour was an independent risk factor for poorer QoL [28]. Results from a qualitative study were similar [24].…”
Section: Challenging Child Behaviormentioning
confidence: 99%
“…Stres u porodicama zavisi od brojnih činilaca: od veličine porodice, karakteristika porodice i deteta, emocionalne klime u porodici, od društvenog konteksta, zabrinutosti za dete i njegovu budućnost (Damjanović, Mihić i Jestrović, 2012), roditeljskih strategija suočavanja sa stresom (McStay, Trembath & Dissanayake, 2014). Stres roditeljstva je generalno usko povezan sa funkcionisanjem roditeljske uloge, zahtevima koji proizilaze iz roditeljstva i kvalitativno je različit u odnosu na stres iz bilo kog drugog domena života (Profaca i Arambašić, 2004).…”
unclassified